Governança da inovação e a criação de valor as melhores práticas para maximizar a competitividade das empresas brasileiras - Andrade, Paulo Roberto Schiavon de (Universidade do Vale do Rio dos Sinos, 2021)
Academic literature has increasingly highlighted the positive correlation between corporate governance and fostering innovation, consequently leveraging value creation and organizational competitiveness. On the other hand, there is still a lack of studies about the functioning of innovation governance, both theoretically and empirically. At the same time, Brazil has shown strong contrasts in terms of the production of innovation. On the one hand, there is a group of innovative companies with a long history of outstanding competitiveness at a national and international level. In contrast, most national organizations do not encourage innovation. Thus, through a selection of eight companies headquartered in Brazil, recognized as competitive and innovative, twenty-one semi-structured interviews were carried out - with twenty-four executives - and extensive documentary research, which allowed to identify and understand common patterns in policies and functional innovation governance procedures for these organizations. The result demonstrates that, unlike traditional theoretical governance models that try to explain the efficiency of companies through disciplinary or knowledge-based actions, innovation governance promotes the creation of value by acting on three management fronts: corporate relationships; the development of organizational skills; and a portfolio of innovation initiatives. The optimization of the joint action of these activities enables the potentization of innovation and competitiveness in organizations. Therefore, it was possible to suggest theoretical concepts for shaping a specific model of governance of innovation and propose eight practices that can serve as a guide for Brazilian companies to leverage innovation and maximize their long-term competitiveness.
Keywords: Governança da inovação; Criação de valor; Competitividade; Empresas brasileiras; Governance of innovation; Value creation; Competitiveness; Brazilian companies; ACCNPQ::Ciências Sociais Aplicadas::Administração